Analisa Pengelolaan Sampah di Kecamatan Namo Rambe Kabupaten Deli Serdang - Heryani br Keliat; Zulkarnaen Lubis; Budi Hartono (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
Waste management in Namo Rambe Sub-district is not optimal, waste is not managed by the government, and piles and scattered garbage can be seen in corners of settlements/housings and illegal waste collection places as well as public facilities. This study aims to identify and analyze waste management which includes 5 (five) mutually supportive aspects consisting of legal and regulatory aspects, institutional aspects, operational technical aspects, financing aspects, and community participation aspects, and to identify and analyze obstacles in waste management in Namo Rambe District, Deli Serdang Regency. The research used was descriptive method, and the data analysis technique used descriptive qualitative. The results showed that waste management in Namo Rambe District was still classified as not good, because of the five aspects of waste management based on the theory of SNI-3242-2008, there were several aspects that were still not implemented properly, namely: legal and regulatory aspects, institutional aspects, technical aspects. operational and community participation aspects. There are obstacles faced by the government in waste management, it is necessary to make regulations regarding the number of waste management costs, add infrastructure, establish cooperation between interrelated institutions from the center to the regions, allocate the required costs and be more active in socializing by appealing to increase awareness public.